Recycling of the actin monomer pool limits the lifetime of network turnover. (13th March 2023) - Colin, Alexandra; Kotila, Tommi; Guérin, Christophe; Orhant‐Prioux, Magali; Vianay, Benoit; Mogilner, Alex; Lappalainen, Pekka; Théry, Manuel; Blanchoin, Laurent
Abstract: Intracellular organization is largely mediated by actin turnover. Cellular actin networks continuously assemble and disassemble, while maintaining their overall appearance. This behavior, called "dynamic steady state, " allows cells to sense and adapt to their environment. However, how structural stability can be maintained during the constant turnover of a limited actin monomer pool is poorly understood. To answer this question, we developed an experimental system where polystyrene beads are propelled by an actin comet in a microwell containing a limited amount of components. We used the speed and the size of the actin comet tails to evaluate the system's monomer consumption and its lifetime. We established the relative contribution of actin assembly, disassembly, and recycling for a bead movement over tens of hours. Recycling mediated by cyclase‐associated protein (CAP) is the key step in allowing the reuse of monomers for multiple assembly cycles. ATP supply and protein aging are also factors that limit the lifetime of actin turnover. This work reveals the balancing mechanism for long‐term network assembly with a limited amount of building blocks. Synopsis: Mechanisms enabling the maintenance of cellular structural stability during the constant turnover of a limited actin monomer pool are poorly understood. Here, reconstitution of actin in a dynamic steady state using a combination of purified proteins and cell‐sized compartments reveals the parameters influencing actin lifetime. Sustained actin turnover over multiple hours was reconstituted in cell‐sized microwells containing a limited amount of components A recycling step is required for reuse of actin monomers and other actin‐binding proteins in multiple assembly cycles Actin monomers age and limit the lifetime of the reconstituted system Changes in the availability of actin monomers enable a feedback loop between assembly and disassembly Abstract : Reconstitution of actin in a dynamic steady state using cell‐sized compartments reveals the parameters influencing long‐term assembly upon limited component availability.